Cairo declaration of human rights: viability as an Islamic alternative declaration - Haneef, Sayed Sikandar Shah (2013)
Cairo Islamic Declaration of Human Rights which enjoys some semblance of legitimacy before the world body definitely represents Muslims` “protest” against those provisions of the Universal Declaration of Human Rights which glaringly contradict some of the most endeared principles of Muslim Law.Sentimentally, it is a credible attempt but its viability to enhance and protect most basic rights as enjoined by Shari`ah in Muslim countries is a matter of academic debate. Critics believe that it neither has the capability to rival the western inspired scheme of rights nor is able to stop transgression against human rights within localities which it represents. Accordingly, its retention or abdication has its own opponents and proponents. This paper, therefore, offers a critical analysis of the internal debate on the declaration with the purpose of identifying the option in perspective.